Comparison of WSM and Weight Product Methods with WSM-Score and Vector Approaches - Roziyani Setik; Asyahri Hadi Nasyuha; Sri Redjeki (International Journal of Informatics and Data Science, 2024)
Fertilizer is a material that is given to the soil or plants to meet the nutritional needs of the plant. Fertilization needs to be carried out rationally according to the needs of the plant. In the supply of fertilizers, farmers have difficulty in determining the best fertilizer for their plants, making it difficult to choose which fertilizers are good for their plants. In determining the best fertilizer, the decision support system (DSS) can be used as an alternative to help someone make decisions more effectively and efficiently by utilizing certain data and models. To solve the existing problems, it is necessary to conduct research in decision making using the Weighted Sum Model (WSM) and Weight Product (WP) Methods which can produce decisions based on the best fertilizer criteria that will be purchased by customers. The Weighted Sum Model (WSM) method is one of the simplest and easiest methods to understand its application, this method is also part of the MCDM (Multi-Criteria Decision Making) method in evaluating the value of each alternative. The Weight Product (WP) method is a method using multiplication to relate the attribute rating, where the rating of each attribute must be ranked with the attribute weight in question. From the results of the implementation of this system, it can be concluded that using the Weighted Sum Model and Weight Product method can help customers in the decision-making process for choosing the best fertilizer to use on their plants.